Posłuszeństwo monastyczne w prawodawstwie pachomiańskim i bazyliańskim - Ciemała, Marianna (Vox Patrum, 2016)
Obedience was one of the fundamental principles of community life in monasteries in the first centuries. Based on the analysis of the texts of St. Pachomius’ and St. Basil’s legislation, the article addresses the issue of different correlations taking place within the framework of monastic obedience. The texts of the Rule of St. Pachomius as well as of the Asketikon of St. Basil the Great show that in the cenobitical life there was a close relationship between obedience to God, to His word, to the rule of life, to superiors, and, to some extent even to all brothers. Sacred Scripture was considered the primary, or even the only, rule of life for the cenobites. Both the Pachomius and Basil in their Rules put a strong accent on obedience to God, which, in practice, was realized in keeping His commandments. The main role of superiors was to lead the brothers to the fullness of salvation. They were to do it with care and responsibility. The analysis of the texts on superiors found that they indicated that the superiors had the obligation to be the first in keeping the God’s commandments as well as in obeying the Rule and the precepts of the elders. Obedience to superiors was understood as being the same as obedience to God, but was dependent according to the way the superiors fulfill their dutes of preaching the word of God and living their lives in agreement to their teaching.